Responsivity of the Striatal Dopamine System to Methylphenidate—A Within-Subject I-123-β-CIT-SPECT Study in Male Children and Adolescents With Attention-Deficit/Hyperactivity Disorder - Aster, Hans-Christoph; Romanos, Marcel; Walitza, Susanne; Gerlach, Manfred; Mühlberger, Andreas; Rizzo, Albert; Andreatta, Marta; Hasenauer, Natalie; Hartrampf, Philipp E.; Nerlich, Kai; Reiners, Christoph; Lorenz, Reinhard; et al. (Frontiers in Psychiatry, 2022)
Background: Methylphenidate (MPH) is the first-line pharmacological treatment of attention-deficit/hyperactivity disorder (ADHD). MPH binds to the dopamine (DA) transporter (DAT), which has high density in the striatum. Assessments of the striatal dopamine transporter by single positron emission computed tomography (SPECT) in childhood and adolescent patients are rare but can provide insight in how effects of MPH affect DAT availability. The aim of our within-subject study was to investigate the effect of MPH on DAT availability and how responsivity to MPH in DAT availability is linked to clinical symptoms and cognitive functioning. Methods: Thirteen adolescent male patients (9-16 years) with diagnosis of ADHD according to DSM-IV and long-term stimulant medication (for at least 6 months) with MPH were assessed twice within 7 days using SPECT after application of I-123-ß-CIT to examine DAT binding potential (DAT BP). SPECT measures took place in on and off-MPH status balanced for order across participants. A virtual-reality continuous-performance test was performed at each time point. Further clinical symptoms were assessed for baseline off-MPH. Results: On-MPH status was associated with a highly significant decrease (-27,6%) of striatal DAT BP as compared to off-MPH (t=4.93, p<0.001). More pronounced decrease in striatal DAT BP was associated with higher off-MPH attentional and externalizing symptom ratings (Pearson r=0.68, p=0.01). Striatal DAT BP off-MPH, but not on- MPH, was associated with higher symptom ratings off-MPH (Pearson r=0.56, p=0.04). In further exploratory analysis in left vs. right striatal sub-regions, stronger decrease in DAT BP in the right caudate nucleus was weakly associated with improved performance in the continuous-performance test (Pearson r= - 0.54, p=0.07). Conclusion: Our findings corroborate previous reports from mainly adult samples that MPH reduces striatal DAT BP availability and suggest higher off-MPH DAT BP, likely reflecting low baseline DA levels, as a marker of symptom severity. More speculatively, regional specific responsivity of DAT BP to MPH may reflect treatment response with respect to cognitive functioning. However, implications from this small patient sample should be treated with caution and warrant replication.